The Beth-Shemesh Tablet in Alphabetic Cuneiform - Albright, W. F.
vgl. bereits E. Grant, BASOR 52 (1933) 4-5; G. A. Barton, BASOR 52 (1933) 5-6; W. F. Albright, BASOR 52 (1934) 18-19 und ‛Ain Shems III (1934) p. 29, fig. 2A, and pl. XX.